Health Care Chat-Bot Using Artificial Intelligence and Machine Learning - Mohan Kumar B K; Praveen S R; Mahesh R; Manoj Gowda M N; Dhanush T C (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Automatized medical chat bots are conversationally built with technology in mind with having the potential to reduce efforts to healthcare cost and improve access to medical services and knowledge. We build a diagnosis bot that engages patients in the conversation for their medical queries. Our chatbot system is qualified to identify symptoms from user input with a standard prediction of 65% - 70%. We have critically and exhaustively analysed recent research and review papers that a pertinent to AI based health care chatbots. Based on the basic concepts used in their mechanisms, the existing approaches are categorized. The emphasis is on the concept used by the concerned authors, the methodology used for experimentations and the performance evaluation parameters. The claims of the researchers are also highlighted. Our findings from the exhaustive literature review are mentioned along with the identified problems. This project is very important for the comparative study of various healthcare chatbots approaches which is prerequisite for solving remote health issues. In the end, we’ve proposed our own chatbot pertaining to the health care system. We have blended AI with ML. We have implemented the idea wherein one can easily and readily diagnose the disease or illness and the details can be provided remotely before consulting a medical practitioner or visiting a doctor.